2015
DOI: 10.1096/fj.14-265009
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 14‐3‐3 in tubulin instability and impaired axon development is mediated by Tau

Abstract: 14-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 69 publications
(111 citation statements)
references
References 57 publications
(82 reference statements)
5
102
0
Order By: Relevance
“…We then characterized the interaction of MAP2c with 14-3-3 at a molecular level, and we studied the effect of 14-3-3 on tubulin polymerization induced by MAP2c. We found that the same regions of unphosphorylated MAP2c and Tau interact with 14-3-3 and that the binding affinity of MAP2c is greatly increased by phosphorylation, as described previously for Tau (25,39). However, NMR analysis of the phosphorylation kinetics revealed that, despite their highly homologous sequences, PKA phosphorylates MAP2c and Tau in a different manner.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…We then characterized the interaction of MAP2c with 14-3-3 at a molecular level, and we studied the effect of 14-3-3 on tubulin polymerization induced by MAP2c. We found that the same regions of unphosphorylated MAP2c and Tau interact with 14-3-3 and that the binding affinity of MAP2c is greatly increased by phosphorylation, as described previously for Tau (25,39). However, NMR analysis of the phosphorylation kinetics revealed that, despite their highly homologous sequences, PKA phosphorylates MAP2c and Tau in a different manner.…”
supporting
confidence: 82%
“…14-3-3 proteins are proposed to be involved in the phosphorylation-dependent control of microtubule dynamics by competing for phosphorylated Tau with tubulin (24,39,40). PKA seems to be the key kinase in this mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our results (Figs. 3B and 3C) showed that the diabetic pathophysiological factors could upregulate ROCK1 and 14-3-3σ which are associated with neurodegeneration [32, 33]. Thus it would be interesting to investigate whether ROCK1 or 14-3-3σ is a link between type 2 diabetes and Alzheimer's disease which shows an increased risk in type 2 diabetes [34].…”
Section: Discussionmentioning
confidence: 99%
“…118,119 Previously, we solved the crystal structure of 14-3-3 in complex with synthetic peptides comprising the phosphorylation sites pSer214 and pSer324. 120 The sequence surrounding pSer214 ( 211 RTPpSLPTP 218 ) is especially interesting with three proline residues as notable structural features ( Figure 8A). In particular, Pro218 occupies a position that is not used by most of the other structurally elucidated 14-3-3 recognition motifs.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%